A systematic literature review of the influence of the university's environment and support system on the precursors of social entrepreneurial intention of students - Carlos Bazan; Hannah Gaultois; Arifusalam Shaikh; Katie Gillespie; Sean Frederick; Ali Amjad; Simon Yap; Chantel Finn; James Rayner; Nafisa Belal (Journal of Innovation and Entrepreneurship, 2020)
This systematic literature review aims at understanding the influence of the university's environment and support system (ESS) in shaping the social entrepreneurial intention (SEI) of post-secondary education students. Social entrepreneurs play an important role in the economic and social developments of the communities in which they operate, thus many post-secondary institutions are starting to encourage more students to engage in social entrepreneurial behaviour. Consequently, there is a need for systematic approaches to evaluate the impact of various motivational factors related to the university's entrepreneurial ecosystem that could affect the SEI of students. Based on a systematic literature review and narrative synthesis of the antecedents of the SEI of post-secondary education students, the authors proposed a customized SEI model that modifies and extend the one proposed by Hockerts (Entrepreneurship: Theory and Practice, 2017) and Mair and Noboa (Social entrepreneurship, 2006). This study fills a gap in the literature by providing a methodology grounded in theory that can help universities to design their educational and other interventions aimed at encouraging more students to consider social entrepreneurship as a viable career choice after graduation
Keywords: 650; Social entrepreneurial intention; University environment and support system; Student social entrepreneurs; Systematic literature review